E-Service Quality: an Empirical Study of The Halo Application at Aisyiyah Hospital Bojonegoro - Daffa, Ahmad Sultan; Kumalasari, Ana; Rupiarsieh, Rupiarsieh (Universitas Muhammadiyah Gorontalo, 2024)
Providing adequate facilities to prioritize patient needs to obtain optimal health services, the Halo RSA application appears as a big step. The author sees empowerment in the side of health services through this digitalization steps provided to improve the performance of Aisyiyah hospital services, realize excellent service, and increase patient satisfaction. Improvement in service quality is given based on the less than optimal conventional services received by patients. With this application, the aim is to reduce public stigma towards health services which in fact take too long, are messy and even less responsive. However, despite the sophistication offered through digital service applications, problems are often still found in their application. Where, when patients or users use the Halo RSA application, there are features that experience bugs or errors, mismatches in registered queue numbers, and inpatient room registration. This research uses a qualitative type with a case study approach on the Halo RSA application. The research theory used by the Delone & McLean IS (D&M IS) Model to see the level of success of the Halo RSA application. Based on the results of research in the field, the Halo RSA application is able to meet standard indicators for each dimension where in its application they influence each other and there is a reciprocal relationship between patient and user satisfaction with Aisyiyah Hospital health services through the various features provided